Science ASSISTments: Tutoring Middle School Students' Inquiry Skills in the Domain of - State Change - DiTullio, Steven Michael (Worcester Polytechnic Institute, 2010)
This paper outlines the development effort and a small pilot study conducted to assess students' understanding of state change in order to: - 1) characterize middle school students' inquiry skills, - 2) develop an effective set of tutoring prompts for inquiry within a technical environment, and - 3) determine the effectiveness of various prompts and scaffolding tasks at improving inquiry skills. -